2015
DOI: 10.3109/17538157.2015.1033528
|View full text |Cite
|
Sign up to set email alerts
|

Case management for frail older adults through tablet computers and Skype

Abstract: Using Skype and tablet PCs do have potential for frail older adults, but need to be tested further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…59 If health is a reason for a decline in mastery, a focus should be on establishing how the Internet might provide support so as to counteract a decline in sense of mastery. Conversely, studies have indicated that not knowing how to use the Internet well can be stressor in itself for an older adult, 10,60 which could trigger a decline in mastery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 If health is a reason for a decline in mastery, a focus should be on establishing how the Internet might provide support so as to counteract a decline in sense of mastery. Conversely, studies have indicated that not knowing how to use the Internet well can be stressor in itself for an older adult, 10,60 which could trigger a decline in mastery.…”
Section: Discussionmentioning
confidence: 99%
“…A study on tablet computers and Skype use by frail older adults indicated that if an older person felt too frail or ill, this was a barrier to starting to use new technology. 10…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty prevalence measured with the Phenotype of Frailty score was reported to be 15%, 10%, and 7.4% in the USA, 54 Europe, 55 and Japan, 56 respectively. We found that research work in digital health technologies for PLF were mostly concentrated in regions with a high frailty prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have expressed some concerns about privacy and security and ease of use of the technology [37,38]. Some studies have reported less enthusiasm for video consultations among older people [39,40]. Qualitative studies have reported concerns over technical issues such as pixilation or audio quality and quality of care, for instance, because of the lack of physical examination [9,38,41,42].…”
Section: Introductionmentioning
confidence: 99%